The Replication Dilemma Unravelled: How Organizations Enact Multiple Goals in Routine Transfer - D’Adderio, Luciana (Organization Science, 2014)
I examine how organizations address the replication dilemma by simultaneously enacting contrasting goals while transferring routines across complex organizational settings. I address this issue by drawing on a qualitative case-based inquiry into the multiplicity of the routines’ ostensive and performative aspects in the context of routine transfer and exact replication. The subject of inquiry is a leading electronics organization facing the dilemma of how to deal with simultaneous competing pressures to copy exactly (replicate) and change (innovate). I find that organizational members address this dilemma (1) by harnessing artifacts and communities to establish two sets of ostensive patterns and performances, one supporting alignment (replication) and one improvement (innovation), and (2) by striving to maintain a dynamic balance between them by enacting them in different proportions. This allows offsetting competing goals and the related pressures both at specific points in time and over time. Building on these findings, I develop a theoretical framework that adds to the extant replication and routines literatures, and the Carnegie account of routine transfer and goal balancing, by capturing (1) the microlevel, performative dynamics by which organizations unravel the replication dilemma in routines transfer while addressing competing goals and the associated pressures and (2) the role of the social and material features of context in the (re)production and transfer of routines.